Land Cover Mapping Using Remote Sensing Data: a Case Study for Chimmony Wildlife Sanctuary - Suraj, M. A.; Menon, A. R. R.; Varghese, A. O.; Suresh Babu, P. K.; Kumar, M. Pradeep (Indian Forester, 1997)
Land cover maps depicting various vegetation cover classes are highly necessary for sanctuary management. Remote Sensing Data utilization for cover type mapping is one of the most cost effective method for vegetation mapping, especially in tropics. Here an attempt is made to map the forest vegetation of Chimmony Wildlife Sanctuary using aerial photographs (Black & White 1:15,000) and Landsat TM FCC (1:50,000) using the standard visual interpretation techniques.